Implant comparisons for finishing steers - S. Laudert; Gerry L. Kuhl; M. Walker (Kansas Agricultural Experiment Station Research Reports, 1984)
A one hundred and forty day field trial was conducted to evaluate the relative performance of steers implanted with Compudose, Ralgro and Synovex-S. Daily gains of cattle receiving a single initial implant were increased 8.0% with Compudose, 12.7% with Ralgro and 21.5% with Synovex-S compared to non-implanted controls. Steers on a reimplant program with Ralgro and/or Synovex-S gained 23.6 to 24.9% faster than controls, with no significant difference due to implant brand or sequence.
Keywords: Cattlemen' s Day; 1984; Kansas Agricultural Experiment Station contribution; no. 84-300-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 448; Beef; Implant; Performance; Gain